Power quality management using statcom for grid interfaced wind turbine controlled by microcontroller - Singh Panwar, Mohan; Ajay Kumar Bansal, Dr. (International Journal of Engineering and Technology, 2018)
Input source for wind power generation in wind turbine is wind. Variation of wind is uncontrolled. Quality of power gener- ated in a windmill is very poor due to uncontrolled and fluctuated nature wind. As per International Electro-technical Commission standard, IEC-61400 norms the power quality and measurements of wind turbine is to be calculate. Electrical energy generated from wind power is based on minimum pollution of environment as comparative to conventional sources of generation. In a grid connected wind power system there are some power quality issues. In grid integrated wind power systems, quality of power is measured by active power, reactive power & variation of voltages measured under guidelines of national & international standards. In this proposed system, the energy generated by wind turbine is converted to DC & DC bus is charged. A microcontroller regulated PWM inverter convert this DC voltage to AC to feed it to grid. The pro- posed DC Bus is augmented by PV (photovoltaic) charged Battery Based PWM controlled STATCOM.Â